Penguatan Kompetensi Calon Guru Terhadap Mahasiswa PPL di SMKN 1 Sangatta Utara - Muhammad Ibnu Faruk Fauzi; Muhammad Fadhil Ramadhan (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
This study aims to examine the strengthening of teacher competencies among student teachers participating in the Field Experience Practice (PPL) at SMKN 1 Sangatta Utara, which is a partner school of STAI Sangatta. The background of this research is based on the importance of teacher competencies in the era of Education 4.0 and the strategic role of the PPL program in equipping prospective teachers with adequate pedagogical, professional, social, and personal competencies. The research employed a qualitative approach with a phenomenological method, utilizing interviews, observations, and documentation as data collection techniques. The results of the study indicate that the PPL program at SMKN 1 Sangatta Utara is effective in developing the four key competencies of prospective teachers: pedagogical, professional, social, and personal. This competency strengthening includes the ability of students to design student-centered learning, develop communication skills, and integrate technology into teaching. This research is expected to contribute to the improvement and development of the PPL program in the future and serve as a reference for other higher education institutions in preparing competent and adaptive prospective teachers in the digital era.